Enhanced Surveillance of Norovirus Outbreaks of Gastroenteritis in Georgia - Widdowson, Marc-Alain (Association of Schools of Public Health, 2011)
OBJECTIVES: The role of noroviruses in both foodborne and person-to-person outbreaks of acute gastroenteritis (AGE) has been difficult to determine in the U.S. because of lack of routine norovirus testing and of national reporting of person-to-person outbreaks. We conducted a prospective study in one state in which enhanced testing for noroviruses was performed to better understand the relative contribution of all gastroenteric pathogens. METHODS: During the two-year period, 2000–2001, we took all fecal specimens from AGE outbreaks reported in Georgia that were negative for bacteria and tested these for norovirus. RESULTS: We investigated 78 AGE outbreaks, from which suitable fecal samples were collected from 57 of them. Norovirus was identified in 25 (44%) outbreaks, bacteria in 20 (35%) outbreaks, and parasites in one (2%) outbreak. Forty-three (75%) of the outbreaks tested were foodborne, of which 17 (40%) were attributable to norovirus and 18 (42%) were attributable to bacteria. Adjusting for incomplete testing, we estimated that 53% of all AGE outbreaks were attributable to norovirus. A total of 2,674 people were reported ill in the 57 outbreaks, and norovirus infections accounted for 1,735 (65%) of these cases. Norovirus outbreaks tended to be larger than bacterial outbreaks, with a median number of 30 vs. 16 cases per outbreak, respectively (p=0.057). CONCLUSIONS: This study provides further evidence that noroviruses are, overall, the most common cause of AGE outbreaks in the U.S. Improved specimen collection, reporting person-to-person outbreaks, and access to molecular assays are needed to further understand the role of these viruses and methods for their prevention.